2015
DOI: 10.1002/lno.10051
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in nitrogen and phosphorus concentrations in the Hii River as influenced by atmospheric deposition from East Asia

Abstract: Deposition of atmospheric nutrients is known to alter oligotrophic ecosystems such as the open ocean, but the role of such nutrients in the further deterioration of eutrophic aquatic ecosystems is largely unknown. The Hii River watershed in Japan encompasses lagoons that have been eutrophic since 1980s. This study examined the atmospheric deposition of nitrogen and phosphorus in the Hii River watershed and the nitrogen and phosphorus concentrations in the Hii River over an 11-yr period. Total nitrogen (TN) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The cascades of effects due to anthropogenic shifts in N:P ratios are similar in aquatic systems (lakes, estuaries, streams) and terrestrial ecosystems, where water and planktonic N:P ratios tend to increase in response to atmospheric deposition, leading to lower “growth rates,” complexity of community structure, and trophic diversity (Figure ; Table S1). Exceptions to these trends, however, have been recorded for aquatic systems, such as a decrease in N:P ratios in Japan due to the increasing deposition of P from dust dispersed from countries in southeastern Asia (Miyazako et al, ), and for European and North American lakes in areas with recent reductions in N deposition (Gerson et al, ; Isles et al, ). Although most studies of urban and crop wastes and leachate loads to rivers and estuaries (83.3%) have found increasing N:P ratios associated with increasing N:P ratios from human inputs, other studies (13.7%) tended to find decreasing ratios in areas with high livestock densities (Arbuckle & Downing, ; Johnson, Heck, & Fourqurean, ; Figure ; Table S1).…”
Section: Impacts Of Shifts In the N:p Ratios Of Human Inputs On Organmentioning
confidence: 99%
See 1 more Smart Citation
“…The cascades of effects due to anthropogenic shifts in N:P ratios are similar in aquatic systems (lakes, estuaries, streams) and terrestrial ecosystems, where water and planktonic N:P ratios tend to increase in response to atmospheric deposition, leading to lower “growth rates,” complexity of community structure, and trophic diversity (Figure ; Table S1). Exceptions to these trends, however, have been recorded for aquatic systems, such as a decrease in N:P ratios in Japan due to the increasing deposition of P from dust dispersed from countries in southeastern Asia (Miyazako et al, ), and for European and North American lakes in areas with recent reductions in N deposition (Gerson et al, ; Isles et al, ). Although most studies of urban and crop wastes and leachate loads to rivers and estuaries (83.3%) have found increasing N:P ratios associated with increasing N:P ratios from human inputs, other studies (13.7%) tended to find decreasing ratios in areas with high livestock densities (Arbuckle & Downing, ; Johnson, Heck, & Fourqurean, ; Figure ; Table S1).…”
Section: Impacts Of Shifts In the N:p Ratios Of Human Inputs On Organmentioning
confidence: 99%
“…Atmospheric P deposition is also increasing due to the rising levels of anthropogenic emissions of P to the atmosphere (3.5 Tg P/year), which have led to current net continental and oceanic rates of P deposition of 2.7 and 0.8 Tg P/year, respectively (Wang, Balkanski, et al, 2015). This deposition has been particularly intense in areas of the world with emerging economies, such as eastern Asia, which may account for the low N:P ratios reported in some freshwater systems in Japan (Miyazako et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The atmospheric deposition is one of the potential nutrient sources and is important in regulating the phytoplankton biomass in an estuary (Yadav et al, 2016). Atmospheric deposition of TN and TP display annual cycles (Miyazako et al, 2015). Compared with other source paths of nutrients into the PRE, the contribution of atmospheric dry and wet deposition was relatively low (Supplementary Table 2; Li et al, 2011), accounting for 12.64% of TN and 1.14% of TP.…”
Section: Atmospheric Depositionmentioning
confidence: 99%
“…Since TN and TP concentrations increased with increasing precipitation and discharge (Figures S3 and S4), our results in agricultural and residential areas indicate that drainage water from a small area of anthropogenic land covers (Figure S5) enriches TN and TP concentrations in river water during storms. Miyazako et al () reported an increasing trend of the atmospheric TP deposition in the basin over the past decade, which in turn affected the atmospheric ratio of TN to TP, and explained that this trend may have increased the phosphorus leakage from the soil. These may in turn persist at the present level or increase the concentrations of TN and TP and the eutrophic level in downstream rivers and waters.…”
Section: Discussionmentioning
confidence: 99%